The evaluation of Disaster Resilient Village Program to support National Security matters - Widana, I Dewa Ketut Kerta; Bahar, Fauzi; Mayori, Ersha; Bimo, Emanuel Ario (Technium Social Sciences Journal, 2022)
Disaster Resilient Village is a village with capability to independently adapt and deal with disaster threat, and quickly recover from the adverse effect of disaster. This research employed Context, Input, Process, and Product (CIPP) evaluation model to evaluate the Disaster Resilient Village program in Tanjung Benoa Village. As the result, the Context aspect of the Disaster Resilient Village program in Tanjung Benoa Village is appropriate in accordance with the Regulation of the Head of the National Disaster Management Agency of the Republic of Indonesia Number 1 of 2012. On the Input aspect, Tanjung Benoa village has established a Disaster Risk Reduction Forum that consists of the local community representatives. On the Process aspect, the village has developed Disaster-Safe School and Communities that routinely conduct simulations on monthly basis and collaborate with the hospitality sector to develop evacuation sites in the event of a tsunami disaster. On Product aspect, namely community capacity building and community participation, the program resulted in the increasing trust among domestic and foreign tourists and the improvement of Tanjung Benoa people’s welfare. In conclusion, Disaster Resilient Village program in Tanjung Benoa Village has been going well.